Repairing relationship conflict: how Violation types and culture influence The effectiveness of restoration Rituals - Ren, Hong; Gray, Barbara (Academy of Management Review, 2009)
Building on Goffman's (1967) notion of interaction rituals, we propose a process model, a causal model, and several propositions about effective relationship restoration behavior following relationship conflict. We conceptualize relationship restoration as a ritualistic process triggered by a violation. We identify two types of relationship violations and show how they are linked to different restoration processes. We also argue that culture governs restoration rituals for different violations. Therefore, effective relationship restoration results from an interaction of the disputants’ cultures, the violation type, and the type of restoration mechanism offered.